Loneliness and low fruit and vegetable consumption among adults in Japan - Stickley, Andrew; Shirama, Aya; Sumiyoshi, Tomiki (Frontiers in Public Health, 2024)
Background Loneliness is the distressing feeling that arises when a person's network of social relations is perceived as being inadequate in some way. Research has linked loneliness to a number of detrimental health outcomes. There is also some evidence that lonely individuals are more likely to engage in poorer health behaviors. However, as yet, there has been comparatively little attention paid to the relation between loneliness and dietary behavior. In particular, there has been little focus on the association between loneliness and fruit and vegetable intake. Objective The aim of this cross-sectional study was to examine the association between loneliness and low fruit and vegetable consumption in the Japanese general population. Methods Data were analyzed from 3,410 Japanese adults collected in an online survey in early 2023. Information was obtained on past-week fruit and vegetable consumption with a single-item measure, while loneliness was assessed with the Three-Item Loneliness Scale. Information was also collected on sociodemographic characteristics, physical health status, health-risk behaviors and depressive symptoms. Logistic regression was used to assess associations. Results One in twenty (5.3%) adults reported low fruit and vegetable consumption. In a fully adjusted analysis loneliness was associated with higher odds for low fruit and vegetable consumption (OR: 1.14, 95%CI: 1.04–1.26). In sex- and age-stratified analyses loneliness was significantly associated with low fruit and vegetable consumption in both women and middle-aged adults, although confidence intervals overlapped for this association across all of the sex and age groups in the fully adjusted analyses. Conclusions Loneliness is associated with low fruit and vegetable consumption among adults in Japan. As loneliness and inadequate fruit and vegetable intake have both been linked to poorer health outcomes, the results of this study underscore the potential importance and public health benefits of reducing loneliness in Japan.